Level of Acceptability of Fudge Oreo with Cream Milk (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2020)
Fudge is a type of sugar candy that is made by mixing sugar, butter, and milk; heating it to the soft-ball stage at 240 °F (116 °C); and then beating the mixture while it cools to acquire a smooth, creamy consistency. This study focused on the level of acceptability of fudge Oreo filled with cream milk in the Home Economics (HE) Strand in Bestlink College of the Philippines. The researchers conducted this study because it has many nutrient contents and we want to satisfy customers with the delicious taste and softness of their product. This study used a descriptive research method. We used a survey questionnaire and then tabulated the obtained data. The respondents included 50HE Strandstudents and 6 HE teachers who answered the survey questionnaire, which included questions regarding the taste, aroma, and presentation of the product, that is, fudge Oreo filled with creamy milk. One survey table was removed due to being incomplete. The respondents answered the questionnaires by rating each indication given by putting a check on the space provided that corresponds to their answers. The results showed that the students obtained the average weighted mean of 1.32, with the verbal interpretation of least agreed, while the teachers obtained the average weighted mean of 3.41, with the verbal interpretation of agreed. Future research should explore and understand new and improved products. Given that this research showcased the level of acceptability of the product, it would be interesting to study the level of the feasibility, marketability, and effectiveness of a product. In the future, it will be very important to study consumer psychology in detail for food consumption and purchasing habits to launch new products that will be successful. We hope that future researchers can use this study as a guide for their future research study if they are going to create a similar product.
Keywords: fudge Oreo, cream milk, acceptability